Tribological performance evaluation of organic polymer as additives in vegetable oil using steel materials - Opia, Anthony Chukwunonso; Ali, Audu Ibrahim; Abdollah, Mohd Fadzli bin; Mohd Kameil, Abdul Hamid; Syahrullail, Samion; Mama, Stanly Chinedu; Saleh, Abdelgade Agilah; Sule, Ahmed; Johnson, Charles N (SAGE Publications Ltd, 2023)
An investigation on lubricating oil rheological behavior and tribological effect on sliding contact was conducted. The study employed organic polymer Eichhornia Crassipes carboxymethyl cellulose (EC-CMC) polymer as additive in corn oil (CO) and sunflower oil (SFO). The experiment was performed using high frequency reciprocating rig (HFRR). Analysis on viscosity behavior was done with three samples of EC-CMC concentration (0.5 wt.%, 1 wt.%, and 1.5 wt.%) under 100 ml volume of base CO and SFO samples. Rheological studies on the polymer concentrations show good results with 0.5 wt.%, 1 wt.%, and 1.5 wt.%, but indicated optimal on 1 wt.% EC-CMC especially from temperature beyond 100°C for the two selected lubricants. Under friction and wear analysis, the test was conducted using 1 wt.% EC-CMC. The base lubricants CO and SFO yielded coefficient of friction and wear scar diameter of 0.087, 11.2 × 10−6 mm3/N/m and 0.080, 10.5 × 10−6 mm3/N/m, respectively. During the testing, the use of 1 wt.% EC-CMC blended SFO gives lower coefficient of friction than CO both at base state and inclusion with additive. This yielded COF reduction by 22.5% and 13.8% for 1 wt.% EC-CMC +SFO and 1 wt.% EC-CMC+CO, respectively, but gives better reduction under SAE-5W-30. The analysis concluded that application of 1 wt.% concentration of EC-CMC in base oil lubricant for both SFO and CO significantly enhanced the properties. The utilization of this sustainable product certainly will contribute in solving global pollution challenges